Le national-populisme roumain aux portes de Bruxelles - Sorina Soare (Amnis)
National-populism is a major factor in the Romanian political scene, but it is mainly the Great Romania Party, recently transformed into the Great Romania People Party, that consistently exhibits electoral strength. Despite this strength, fixed boundaries built by the other Romanian parliamentary parties nullify any potential of coalition for the Great Romania People's Party. However, this ostracism indirectly contributes to the overall stability of the Romanian democracy. To fully understand this party, the scholar proposes to make a social-historical analysis based on a three levels perspective: the populist theory, its nationalistic elements and its potential to crack the democratic system. In line with the 2007 EU enlargement, the conclusions of this article lay emphasis on the limits of the changes instituted in 2005 and their influence on a continued national and international ostracism.